Positive cascade effects of forest fragmentation on acorn weevils mediated by seed size enlargement - Bonal, Raul; HERNÁNDEZ, MARISA; ORTEGO, JOAQUÍN; Muñoz, Alberto; ESPELTA, JOSEP M. (Insect Conservation and Diversity, 2012)
Abstract. 1. Today, forest fragmentation is one of the major threats to biodiversity worldwide. In this context, fragmented populations of specialised forest organisms face an increasing risk of extinction because of factors such as local food scarcity. Nonetheless, the role of food availability may differ depending on organism size, which is expected to determine the energy requirements and mobility between fragments. 2. A field study was carried out on Curculio elephas, a forest beetle with low dispersal potential, whose larval development takes place in oak Quercus spp. acorns. 3. For a similar seed crop per tree, acorn size was larger in isolated oaks than in trees located in forest patches. Thus, fragmentation increased local food availability for C. elephas. Larger acorns enabled larval size to increase, a key fitness proxy associated with individual survival, adult size, and potential female fecundity. Indeed, the number of both adults and larvae was higher in isolated trees than in forest patches. 4. In the current scenario of increasing forest fragmentation, the survival likelihood of specialist insects may strongly depend on their ability to adapt to altered environmental conditions. To the best of our knowledge, this is the first study to report on how some forest insects may take advantage of fragmentation-mediated changes to survive in isolated trees. 5. From a conservation perspective, management policies should preserve isolated trees as a source of seeds and fauna for the natural regeneration of forest ecosystems after unproductive farmlands have been abandoned.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn size; Curculio; Forest fragmentation; forest insects; Global change; individual fitness; larval size

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Quercus and Pinus cover are determined by landscape structure and dynamics in peri-urban Mediterranean forest patches - Guirado, Maria; Pino, Joan; Rodà, Ferran; Basnou, Corina (Plant Ecology, 2007)
Successional dynamics in Mediterranean forests have been modulated by anthropogenic disturbances during thousands of years, especially in areas densely populated since ancient times. Our objective is to determine whether pine tree cover (early-successional species) and oak tree cover (late-successional species), used as a surrogate of successional stage of peri-urban fragmented forests in the Valle`s lowlands (Catalonia, NE, Spain), are primarily determined by (1) climate and topography; (2) anthropogenic disturbances; (3) patch structure; or (4) patch dynamics from 1956 to 1993. Quercus spp. and Pinus spp. tree cover were separately recorded on 252 randomly selected plots of 100 m 2 , within forest patches ranging in size from 0.25 to 218 ha. Multiple linear regressions indicated that forest patch history is the most important variable determining oak and pine tree cover: new forest patches showed higher pine and lower oak tree cover than recently split patches (i.e. those that became fragmented from large forest areas after 1956). Patches already existing as such in 1956 (pre-existent patches) showed higher pine cover than recently split patches. Oak cover increased and pine cover decreased with increasing forest connectivity of the patch. Finally, highly frequented forests were related to high cover of pines. Climatic and topographic variables were not signiﬁcant. We conclude that pine and oak cover in these peri-urban forests are mainly determined by recent patch dynamics, but also by the spatial pattern of patches. However, humaninduced disturbance can modulate this as there is some evidence for pine being associated with a high human frequentation.
Keywords: á pinus; á quercus forests; anthropogenic disturbances; anthropogenic disturbances á forest; Forest fragmentation; forests á patch structure; fragmentation á historical dynamics; historical dynamics; patch structure; pinus forests; Quercus forests

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J. (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Effects of forest fragmentation on the winter body condition and population parameters of an habitat generalist, the wood mouse Apodemus sylvaticus: a test of - Díaz, M.; Santos, T.; Tellería, J. L. (Acta Oecologica, 1999)
Three main causal hypotheses have been proposed to explain the inverse relationships between habitat patch size and density of gen- eralist mouse species in fragmented habitats: 1) enhanced habitat conditions as habitat patch size decreases; 2) inhibited emigration of excess indi- viduals in small and isolated habitat patches; and 3). reduced territoriality in small patches because they are occupied temporarily by non- reproductive individuals. From the mechanism underlying each hypothesis, we derived predictions on the effects of fragment size on the body condition of individuals (measured both as absolute body size and as body mass relative to body size) and some demographic parameters of mouse populations redated to reproductive output (sex-ratio and proportions of sexually active and recently-born individuals), and we tested such predic- tions with data from wood mice Apodemus sylvaticus wintering in three Spanish forest archipelagos in which the inverse relationship between for- est patch size and mouse abundance had been previously proven. No differences in average body size or in average body mass relative to body size were detected among fragments. Mouse populations wintering in small fragments showed more male-biased sex-ratios, a larger proportion of sex- ually active adults and fewer juveniles as compared to mouse populations wintering in large fragments nearby. Results clearly rejected the third hypothesis and did not support the second one. It thus seemed that habitat conditions for mice improved as forest fragment size decreased, although the expected positive effects on individuals could have been prevented by relaxed territoriality and increased food resource depletion by denser mouse populations. Bearing in mind the negative effects of dense wood mice populations on the distribution, abundance and population dynamics of forest species, this apparent enhancement of habitat conditions for mice in small forest fragments could have far-reaching conse- quences for the long-term persistence of such fragments.
Keywords: Body condition; Body size; demography; Forest fragmentation; population density; winter; wood mouse

Effects of forest fragmentation on the winter body condition and population parameters of an habitat generalist, the wood mouse Apodemus sylvaticus: a test of - Diaz, M; Santos, T; Tellería, J L (Acta Oecologica, 1999)
Three main causal hypotheses have been proposed to explain the inverse relationships between habitat patch size and density of gen- eralist mouse species in fragmented habitats: 1) enhanced habitat conditions as habitat patch size decreases; 2) inhibited emigration of excess indi- viduals in small and isolated habitat patches; and 3). reduced territoriality in small patches because they are occupied temporarily by non- reproductive individuals. From the mechanism underlying each hypothesis, we derived predictions on the effects of fragment size on the body condition of individuals (measured both as absolute body size and as body mass relative to body size) and some demographic parameters of mouse populations redated to reproductive output (sex-ratio and proportions of sexually active and recently-born individuals), and we tested such predic- tions with data from wood mice Apodemus sylvaticus wintering in three Spanish forest archipelagos in which the inverse relationship between for- est patch size and mouse abundance had been previously proven. No differences in average body size or in average body mass relative to body size were detected among fragments. Mouse populations wintering in small fragments showed more male-biased sex-ratios, a larger proportion of sex- ually active adults and fewer juveniles as compared to mouse populations wintering in large fragments nearby. Results clearly rejected the third hypothesis and did not support the second one. It thus seemed that habitat conditions for mice improved as forest fragment size decreased, although the expected positive effects on individuals could have been prevented by relaxed territoriality and increased food resource depletion by denser mouse populations. Bearing in mind the negative effects of dense wood mice populations on the distribution, abundance and population dynamics of forest species, this apparent enhancement of habitat conditions for mice in small forest fragments could have far-reaching conse- quences for the long-term persistence of such fragments.
Keywords: Body condition; Body size; demography; Forest fragmentation; population density; winter; wood mouse

Vertebrate predation on Holm Oak, Quercus ilex, acorns in a fragmented habitat: effects on seedling recruitment - Santos, T.; Tellería, J. L. (Forest Ecology and Management, 1997)
Rodent and avian consumption of Holm Oak, Quercus ilex, acorns were examined in central Spain during two high-production seasons, 1990-1991 and 1993-1994, in 1 and 3 large stands and in 6 and 10 small stands (0.2-12 ha) respectively, to study the effects of vertebrate predation on seedling recruitment. Previous data indicate that wood mouse abundance is much higher in small stands. Tree size, frequency of acorn-bearing oaks and acorn abundance were similar in the two sizes of forest stands. Overall acorn consumption was 33.7 times higher in the small stands compared to that in the large stands in 1991, and 3.1 times larger in 1994. Consumption of acorns by mice in the small stands was 49 and 95 times greater than that by birds in the first and second year, respectively. Seedling recruitment was significantly higher in the large stands in both study seasons. Regeneration by ramets was roughly similar in small and large stands in both seasons. Thus, predation by mice was apparently responsible for the failure of sexual reproduction in the small stands. The results suggest that vegetative regeneration might be the prevalent reproductive method of Holm Oaks in small forest tracts.
Keywords: acorns; Forest fragmentation; oak; Seedling; Vertebrate predation

Effects of forest fragmentation on a guild of wintering passerines: the role of habitat selection - Tellería, J L; Santos, T (Biological conservation, 1995)
This study analyses the winter colonization of an archipelago of 31 forests (0.1-350 ha) in central Spain by the guild of pariforms (Parus, Aegithalos, Regulus, Sitta and Certhia). Two hypotheses are considered: (a) that birds with similar habitat preferences tend to disap- pear simultaneously with the reduction in forest size, leading to a ‘nested’ pattern of species distribution; or (6) that the species in the smallest forests are a random sample of those found in the larger ones. The results sup- port hypothesis (a). The species that depend on rela- tively scarce resources, such as tree trunks and junipers Juniperus thurifera (Sitta europaea, Certhia brachy- dactyla, Parus cristatus and P.ater) only occupied the largest forests. On the other hand, species that exploit abundant, ubiquitous resources, such as holm oak Quercus ilex foIiage (Regulus ignicapillus and Parus caeruleus), were distributed uniformly throughout all the fragments. These results emphasize the need for a better understand- ing of habitat selection by species when designing conser- vation strategies for fragmented populations.
Keywords: Forest fragmentation; habitat selection; Spain; wintering passerines